Machine learning model for predicting out-of-hospital cardiac arrests using meteorological and chronological data. Issue 13 (17th May 2021) - Nakashima, Takahiro; Ogata, Soshiro; Noguchi, Teruo; Tahara, Yoshio; Onozuka, Daisuke; Kato, Satoshi; Yamagata, Yoshiki; Kojima, Sunao; Iwami, Taku; Sakamoto, Tetsuya; Nagao, Ken; Nonogi, Hiroshi; et al.
Abstract : Objectives: To evaluate a predictive model for robust estimation of daily out-of-hospital cardiac arrest (OHCA) incidence using a suite of machine learning (ML) approaches and high-resolution meteorological and chronological data. Methods: In this population-based study, we combined an OHCA nationwide registry and high-resolution meteorological and chronological datasets from Japan. We developed a model to predict daily OHCA incidence with a training dataset for 2005–2013 using the eXtreme Gradient Boosting algorithm. A dataset for 2014–2015 was used to test the predictive model. The main outcome was the accuracy of the predictive model for the number of daily OHCA events, based on mean absolute error (MAE) and mean absolute percentage error (MAPE). In general, a model with MAPE less than 10% is considered highly accurate. Results: Among the 1 299 784 OHCA cases, 661 052 OHCA cases of cardiac origin (525 374 cases in the training dataset on which fourfold cross-validation was performed and 135 678 cases in the testing dataset) were included in the analysis. Compared with the ML models using meteorological or chronological variables alone, the ML model with combined meteorological and chronological variables had the highest predictive accuracy in the training (MAE 1.314 and MAPE 7.007%) and testing datasets (MAE 1.547 and MAPE 7.788%). Sunday, Monday, holiday, winter, low ambient temperature and large interday or intraday temperature difference were more strongly associated with OHCA incidence than other the meteorological and chronological variables. Conclusions: A ML predictive model using comprehensive daily meteorological and chronological data allows for highly precise estimates of OHCA incidence.